Zoonotic Disease Risk Perception and Infection Control Practices amongst Veterinarians in Kerala, India - T. K. Mithun; S. S. Lal; K. Rajasekharan Nayar (Preventive Medicine: Research & Reviews, 2024)
Introduction: Veterinarians could act as the sentinel for the study of zoonotic diseases. This study evaluates the prevalence of zoonoses amongst Kerala veterinarians and explores infection control measures they use to protect themselves and the factors influencing their infection control practices. Materials and Methods: It is a quantitative cross-sectional study using proportionate sampling with a self-administered questionnaire. Results: About 31.1% of veterinarians experienced symptoms of zoonotic diseases, with dermatophytosis being the most common. Handling tissues, bodily fluids and excretions of animals were the highest risk-carrying procedures. However, the majority of respondents did hand wash, whereas some never properly disposed of used needles. Factors such as heat stress, comfort, cost and time of consultation discouraged one-fourth of participants from using personal protective equipment. Conclusion: Failure to follow infection control practices contributes to the prevalence of zoonoses amongst veterinarians in Kerala. Reasons for this failure include the absence of better policies to address veterinarian’s issues. There is a need for more effective enforcement of infection control policy for the veterinarians.